2004
DOI: 10.1002/bip.20034
|View full text |Cite
|
Sign up to set email alerts
|

Light‐harvesting function of carotenoids in photo‐synthesis: The roles of the newly found 11B state

Abstract: This minireview article highlights the energetics and the dynamics of the 1(1)B(u)(-) and 3(1)A(g)(-) states of carotenoids discovered very recently. Those "hidden" covalent states have been revealed by measurements of resonance-Raman excitation profiles of crystalline carotenoids. The dependence of the energies of the low-lying singlet states, including the 1(1)B(u)(+), 3(1)A(g)(-), 1(1)B(u)(-), and 2(1)A(g)(-) states, on the number of conjugated double bonds (n) is in agreement with the extrapolation of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 37 publications
6
91
1
Order By: Relevance
“…On the contrary, we observe the presence of an intense negative peak around 940 nm, which is a well-known feature of the Car and is associated with PA from S 2 to higher lying states. 18 This signal extends to longer excitation wavelengths where there is a weak tail of the ground state absorption spectrum of the Car. At t = 20 fs, very short time after the end of the pump pulse, we observe a strong increase of the PB(Q x ) features, while PA(S 2 ) does not increase significantly, an indication that loss towards S x partially occurs already during the excitation pulse which continuously creates it.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…On the contrary, we observe the presence of an intense negative peak around 940 nm, which is a well-known feature of the Car and is associated with PA from S 2 to higher lying states. 18 This signal extends to longer excitation wavelengths where there is a weak tail of the ground state absorption spectrum of the Car. At t = 20 fs, very short time after the end of the pump pulse, we observe a strong increase of the PB(Q x ) features, while PA(S 2 ) does not increase significantly, an indication that loss towards S x partially occurs already during the excitation pulse which continuously creates it.…”
Section: Resultsmentioning
confidence: 90%
“…An intermediate state with 1B u − symmetry (named S x ) mediating the S 2 → S 1 IC process has been first postulated theoretically and then experimentally demonstrated. [11][12][13][14][15][16][17][18][19][20] Recently, it has been proposed that when Cars are embedded in the LH2 complexes, S x might play an active role in the EET towards the higher excited state Q x of BChls. 21 Moreover, experimental evidence demonstrated the existence of another intermediate state, named S * , involved in the IC process of the Cars, whose origin and nature are still debated.…”
Section: Introductionmentioning
confidence: 99%
“…21,23,35 It may be, however, that the presence of the 1B − u singlet state below the 1B + u state has been actually observed in pure polyenes much earlier. In 1985 Snyder et al 36 interestingly observed a drastic qualitative change of the polyene fluorescence spectrum upon increasing the size of an all-transpolyene from N = 12 π -electrons to N = 14.…”
Section: B Development Of Polyene Spectroscopymentioning
confidence: 99%
“…Reviews on (proposed) excited-state dynamics and optically forbidden states can be found in refs. [157,171,183,189,190,206].…”
mentioning
confidence: 99%